Hearing Loss due to Carbon Monoxide Poisoning - Mehrparvar, Amir Houshang (Hindawi Publishing Corporation, 2013)
Carbon monoxide poisoning is one of the rare causes of hearing loss which may cause reversible or irreversible, unilateral or bilateral hearing loss after acute or chronic exposure. In this report, we present a case of bilateral sensorineural hearing loss in a secondary smelting workshop worker after an acute exposure to carbon monoxide. This complication was diagnosed by pure-tone audiometry and confirmed by transient evoked otoacoustic emissions. Hearing loss has not improved after 3 months of followup.